Minimum Initial Service Package Readiness Assessment (MRA) for Reproductive Health in the Disaster Situation of Mount Merapi Eruption in Magelang Regency - Rafidha Nur Alifah; Alfiana Ainun Nisa; Efa Nugroho; Sofwan Indarjo; Evi Widowati (Jurnal Kesehatan Masyarakat, 2025)
The Minimum Initial Service Package Readiness Assessment (MRA) was a comprehensive tool used to evaluate a region’s preparedness in delivering priority reproductive health services during emergencies, as outlined in the MISP. In Indonesia, the MRA had only been implemented in four provinces, including Central Java. This study was the first research conducted in Magelang Regency. It aimed to describe the implementation of the Minimum Initial Service Package (MISP) for reproductive health during the Mount Merapi eruption disaster in Magelang Regency. A qualitative approach with a case study design was employed, involving 10 informants from government agencies, non-governmental organizations, and evacuation site managers. Data were collected through observation, in-depth interviews, and document review, with data validity ensured through triangulation of techniques and data sources. The data analysis included data reduction, data display, and conclusion drawing. The findings indicated that MISP implementation in Magelang Regency during the Mount Merapi eruption disaster remained suboptimal, particularly due to the absence of a dedicated reproductive health sub-cluster. Despite good coordination among government agencies, awareness and understanding of MISP among policymakers remained limited. Village midwives played a crucial role in health service provision at evacuation sites. However, socio-cultural constructs that perceived reproductive health issues during disasters as sensitive posed significant challenges.